Examination of pork marketing margins - Ted C Schroeder; J Mintert (Kansas Agricultural Experiment Station Research Reports, 1996)
This study analyzes recent changes observed in pork, farm-to-wholesale and wholesale-to-retail, marketing margins. Although the inflation-adjusted, farm-to-wholesale margin has declined over the last 25 years, the wholesale-to-retail margin has increased. Pork producers need to know why these trends have occurred so they better understand pork marketing margin determinants as they develop policy positions and consider vertical marketing alliances.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Pork marketing margins; Pork price spreads